Relationship between Complex Stability and Biokinetics of 99mTc-Phosphate Compounds - Schiimichen, C.; Körfgen, T.; Hoffmann, G. (Nuklearmedizin - NuclearMedicine, 1980)
The complex inertness of 99mTc-EHDP, -MDP, -PPi and -TriP was determined in vitro by means of protein binding of 99mTc after dilution in a phosphate-buffered albumin solution. Commercially available kits were used. In vitro, 99mTc- EHDP was found to be the most stable complex. The biodistribution of these agents was evaluated in the adult rat; here the less stable 99mTc-MDP proved to be the superior bone imaging agent. It is suggested that the complex inertness and the bone affinity are opposing properties of the 99mTc-phosphate compounds, because the complex must hydrolyse before the phosphate compound and technetium (IV) are deposited separately in bone. Hence, bone imaging with 99mTc-phosphate compounds demands a compromise concerning the stability of these complexes at low ligand concentrations, which among the investigated agents is best accomplished by 99mTc-MDP.